PRESENTATION OF THE FINANCIAL STATEMENTS OF NON-PROFIT ENTITIES BASED ON ISAK 35 AT THE HATI GEMBIRA INDONESIA FOUNDATION - Addiena Maghfira; Alifah Ghaisani Putri; Annisa Nur Listianto; Grace Putri; Anisa Putri Astuti (Transpublika Publisher, 2022)
A non-profit organization is an organization whose primary objective is non-commercial, without any intention of making any profit. ISAK 35 is a guideline in the presentation of financial statements for non-profit oriented entities that has been approved by Board of Financial Accounting Standards of the Indonesian Institute of Accountants (DSAK IAI) and has been implemented since 1st January 2020. This study aims to determine the suitability of presenting financial statements based on ISAK 35 at the Hati Gembira Indonesia Foundation. Data collection techniques using secondary data. This research uses descriptive qualitative method as the method of analysis. The results of this study prove that Hati Gembira Indonesia Foundation has presented financial statements for the 2020 period in accordance with ISAK 35, but further adjustments are needed to produce quality financial reports.